Utilizing School Library to Improve Basic Literacy Skills for Islamic Primary School Students - Akudja, Dewi Permatasari; Mas, Sitti Roskina; Razak, Intan Abdjul; Masaong, Abd. Karim (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2023)
This study aims to describe the use of the school library in facilitating the development of the student’s reading culture, the student’s writing skills, and the students’ speaking skills at MIT AL–ISLAH Integrated Islamic Primary School in Gorontalo City. This research uses a qualitative approach with the type of case study research. Data collection techniques were done through observation, interviews, and document studies. The main informant of this research data was the school principal, while the supporting informants were the teacher in charge of the library and the students. The process of data analysis using data reduction, data presentation, and conclusion. The examination of data validity using data credibility through triangulation of sources and methods. The results showed that developing the reading culture of students through the school’s library was conducted by instilling a reading culture from an early age, not only reading books but also reading the Holy Quran and schedule distribution in the library as well. The use of libraries in developing writing skills was conducted by poetry writing programs, rewriting content read, making stories, reading, writing, arithmetic programs, and mentoring methods in terms of learning. The use of libraries in developing speaking skills was conducted by providing an expression corner to practice speaking, having an outdoor space in the library, and participating in several programs made by the library.